Network Security, Firewalls, and VPNs - Stewart, J. Michael (New york Jones and Bartlett Learning, 2011)
This book provides a comprehensive explanation of network security basics including how the use of firewalls and VPNs
symmetric key
12
Keywords: computer networks; computer security; computer software